The Effect of Cultural and Emotional Intelligence on Mentor and Protege Perceptions of Attitude Homophily and Relationship Quality in Culturally Diverse Mentoring Relationships - (:unkn) unknown (My University, 2015)
Mentoring has become more common in organizations as firms have discovered the benefits of this process, such as the retention and cultivation of employees who create the work and products of the organization. To meet the challenges associated with increasing diversity within organizations, researchers have focused on understanding diverse mentoring relationships (Athey, Avery, & Zemsky, 2000; Clutterbuck & Ragins, 2002; Hardy, 1998; Knouse, Hill, & Webb, 2005; Ragins, 1997). The demographic (e.g., ethnicity, gender, age) and situational (e.g., position, power) disparities between mentors and protégés often make it more difficult for diverse partners to develop quality relationships that are needed to realize the full benefits of mentoring. The purpose of this study is to identify important antecedents (i.e., cultural and emotional intelligence) that may foster a higher level of perceived attitude homophily (or attitude similarity) among diverse mentoring partners as well as higher quality mentoring relationships. Drawing on social information processing theory (Salancik & Pfeffer, 1978), I contend that mentors and protégés who are socially intelligent (i.e., culturally and emotionally) will be better mentoring partners. As a result of the enhanced social intelligence, they will have a higher perception of having the same attitudes as their partners, in turn corresponding to a higher quality relationship with their partners. This model was tested on mentors and protégés (not matched pairs) that were involved in racially and/or ethnically diverse mentoring relationships. The self-reports were used to test regression hypotheses of cultural and emotional intelligence on attitude homophily and perception of mentoring relationship quality. Bootstrapping was done to investigate mediation of attitude homophily on the relationships of cultural intelligence and emotional intelligence on relationship quality. Regression results found significant positive relationships of emotional intelligence on attitude homophily for mentors, and on relationship quality for both mentors and protégés. It also found a significant positive relationship between mentors' metacognitive domain of cultural intelligence and relationship quality. Attitude homophily was also found to have a significant positive relationship to perception of relationship quality for both mentors and protégés. The other hypotheses were not proven through regression, although high and mostly significant correlations existed between all the main constructs of this study in both groups. This study offers several contributions to mentoring research. One is that it examined the mentoring relationship from a fairly new theoretical perspective, social information processing, which may yield new insight into mentoring. It empirically tested a model that is grounded in SIP and validated success criteria of attitude homophily and relationship quality of mentors/protégés with their partners. This study also offers practical contributions. It is possible for organizations to test and train individuals that one is considering for a diverse mentoring relationship in emotional intelligence. The impact of this testing and training may result in higher quality mentoring relationships, which will be beneficial to the mentor/protégé in diverse mentoring relationships.
Keywords: Attitude Homophily; Cultural Intelligence; Diversity; Emotional Intelligence; Mentoring; Mentoring Relationship Quality